Modelo de autómatas celulares para la dinámica de un mercado financiero: estrategias, imitación y estados de ánimo - Martínez, Juan José María (2018)
We present a model of artificial market generated by heterogeneous agents to simulate the stylized facts observed in real markets. This model, from the minimalist approach of a complex system, intended to reproduce these phenomena with minimum cost and generate a parametric heuristic scalable in complexity from a stochastic micro-foundation and a price mechanism that includes bounded rationality, imitation, adaptation and moods.